1998
DOI: 10.1093/clinchem/44.5.924
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymes and fatty acid status in erythrocytes of Down syndrome patients

Abstract: The excess of genetic information in patients with Down syndrome (DS) produces an increase in the catalytic activity of superoxide dismutase (SOD1), an antioxidant enzyme coded on chromosome 21. It has been suggested that an increase in oxidative stress in DS patients may cause adverse effects in the cell membranes through the oxidation of polyunsaturated fatty acids (PUFAs). The aim of this study was to evaluate the cellular antioxidant system by determining the catalytic activity of the SOD1, glutathione per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Module membership for acylcarnitines was heterogeneous with respect to acyl chain length and degree of unsaturation, indicating the process captured in this node may be relatively non-specific. Fatty acid composition has previously been observed to differ between DS patients and non-affected sibling controls (Bueno et al, 2015;Pastor et al, 1998), although, to our knowledge, we are the first to report potential alterations associated with DS-AD versus DS-NAD. In euploid AD patients, alterations of fatty acid metabolism are increasingly understood to impact cognitive and neuropathological outcomes (Snowden et al, 2017).…”
Section: T a B L E 2 Metabolic Pathwaysmentioning
confidence: 66%
“…Module membership for acylcarnitines was heterogeneous with respect to acyl chain length and degree of unsaturation, indicating the process captured in this node may be relatively non-specific. Fatty acid composition has previously been observed to differ between DS patients and non-affected sibling controls (Bueno et al, 2015;Pastor et al, 1998), although, to our knowledge, we are the first to report potential alterations associated with DS-AD versus DS-NAD. In euploid AD patients, alterations of fatty acid metabolism are increasingly understood to impact cognitive and neuropathological outcomes (Snowden et al, 2017).…”
Section: T a B L E 2 Metabolic Pathwaysmentioning
confidence: 66%
“…Thus, although it is uncertain whether increase in superoxide dismutase activity has as mentioned a causal role in the development of Down's syndrome, our results indicate that decrease in superoxide dismutase activity might occur in parallel with the advent of dementia in Down's patients. Pastor et al (1998) had, however, found that the activity of SOD1 decreased with age both in Down's patients and their controls.…”
Section: Discussionmentioning
confidence: 94%
“…Although increased free levels of H 2 O 2 could logically be the result of increased SOD1 activity in Down's syndrome, and consequently give vent to production of the deleterious hydroxyl radical ( ¡ OH) through the Fenton reaction, serious doubt exists whether or to what extent this does in fact occur. Percy et al (1990) and Pastor et al (1998) have shown that the activity of erythrocyte glutathione peroxidase and catalase, the natural scavengers of H 2 O 2 , does increase concomitantly in Down's syndrome to such a degree as to match more or less the increased production of H 2 O 2 . Moreover, the work of Jeziorowska et al (1988) casts doubt on whether increased SOD1 activity is at all caus- ally connected to the aetiology of Down's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased pulmonary blood flow is known to be associated with the increased biosynthesis of PGH 2 from arachidonic acid [Smith et al, 1996; Dubois et al, 1998], which then leads to a balanced increase in both TXA 2 and PGI 2 biosynthesis. However, in DS infants, both peroxide and peroxynitrate biosynthesis are likely to be up‐regulated in the presence of increased SOD activity [De La Torre et al, 1996; Pastor et al, 1998; Pastore et al, 2003]. While peroxide promotes PGH 2 biosynthesis [Smith et al, 1996; Dubois et al, 1998], peroxynitrate inhibits the biosynthesis of PGI 2 , but not TXA 2 , from PGH 2 [Zou and Ullrich, 1996; Zou et al, 1997] consequently, an imbalance in TXA 2 and PGI 2 biosynthesis arises that eventually leads to vasoconstriction and vascular smooth muscle cell proliferation [Ullrich et al, 2001].…”
Section: Discussionmentioning
confidence: 99%